PENGARUH SERVICESCAPE, BRAND AWARENESS, DAN TRUST TERHADAP CUSTOMER LOYALTY PADA BRAND STARBUCKS CITRALAND SURABAYA - Harijono, Hendri; Budiarsi, Sri Yunan; Agung, Deatri Arumsari (JURNAL ILMIAH MAHASISWA MANAJEMEN, 2021)
This study aims to analyze the effect of Servicescape, BrandAwareness, and Trust on Customerr Loyalty in a brand StarbucksCitraland Surabaya. The sampling technique used is non probabilitysampling by means of purposive sampling. The sample used in thisstudy was 190 respondents. The data analysis technique used is SEManalysis with the LISREL program. The results of the study provethat Servicescape, and Brand Awareness, have a significant effect ontrust; Trusts have a significant effect on Customerr Loyalty; Servicescape have a unsignificant effect on Customerr Loyalty and BrandAwareness have a significant effect on Customerr Loyalty. Suggestions from research for Starbucks Citraland Surabaya are to fix theelements of Servicescape, so that consumers have a better shoppingexperience that makes them more trusting and have a high interest inrepurchasing